The Effect of Leadership Style, Work Motivation, and Work Discipline Employee Performance at PT. Fadhil Genteng - Salim; Lia Amalia (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to understand and study the effect of leadership style, work motivation and work discipline on the performance of employees of PT. Fadhil Genteng simultaneously and partially. To find out which variable of leadership style, work motivation and work discipline is more dominant in influencing the performance of employees of PT. Fadhil Genteng. In this study, primary data and quantitative approaches were used. The population used in this study were all employees of PT. Fadhil Genteng, totaling 120 people. The data were collected using a questionnaire by distributing online to employees of PT. Fadhil Genteng. The data was then processed using multiple linear regression methods. The results of the analysis that have been obtained show that leadership style, work motivation and work discipline simultaneously or jointly affect the performance of employees of PT. Fadhil Genteng. Partially, leadership style, work motivation and work discipline have a positive influence on the performance of employees of PT. positive influence on the performance of employees of PT. Fadhil Genteng. Then in the results of this analysis, work discipline is a more dominant variable in influencing the performance of employees of PT. affect the performance of employees of PT. Fadhil Genteng